Canine Transmissible Venereal Tumor - Sathish Kumar M1; Poobitha S 2; Ramajayan P 3 (Zenodo, 2022)
Canine Transmissible Venereal Tumor (CTVT) is a contagious neoplasm which is transmitted between dogs as an allogenic graft. The neoplastic cells originate from normal cell that has undergone tumourigenic transformation as a result of genetic mutations. It is the oldest and most prolific neoplasm lineage known in nature, which evolved 11,000 years. CTVT affects the genital and extra-genital sites of both sexes and is transmitted by allogenic transfer of viable neoplastic cells during coitus or by biting, scratching or licking the affected areas by the transplantation of tumor cells. It is most common in dogs aged 2 to 5 years and the incidence is high in females compared to males. It is homogenously distributed in India and reported in all parts of the world, except Antarctica. CTVT escape from the host immune mechanism by not expressing the MHC molecules on the cell surface. The neoplasm undergoes three different stages includes progressive phase, stable phase and regressive phase. Clinical signs include bloody discharge from the genital region and cauliflower- like growth in the genital region of both sexes. Diagnosis of this tumor by examination of cytology, histopathology and molecular confirmation. Cytology is the gold standard method of diagnosis, in which neoplastic cells are round with oval or round nucleus with one or two nucleoli and cytoplasm have punctuate vacuoles and fine granules. In histopathology, CTVT characteristically presents as a group of compact masses of diffusely arranged round or polyhedral cells with a centrally located nucleus and having punctuate vacuoles in the cytoplasm which are supported by thin trabeculae of fibrovascular tissue. CTVT cells are aneuploid, having stable karyotype of 57–59 chromosomes compared to normal chromosome number of dog. The CTVT cells are marked by the presence of Long Interspersed Nuclear Element (LINE-1) insertion close to the c-myc gene and homozygous loss of the CDKN2A (Cyclin Dependent Kinase Inhibitor 2A) gene.